Effectiveness of Domain-Based Intervention for Language Development in Japanese Hearing-Impaired Children: A Multicenter Study. (July 2014) - Sugaya, Akiko; Fukushima, Kunihiro; Kasai, Norio; Ojima, Toshiyuki; Takahashi, Goro; Nakagawa, Takashi; Murai, Seiko; Nakajima, Yasoichi; Nishizaki, Kazunori
Objective: Decreasing language delay in hearing-impaired children is a key issue in the maintenance of their quality of life. Language training has been presented mainly by experience-based training; effective intervention programs are crucially important for their future. The aim of this study was to confirm the efficacy of 6-month domain-based language training of school-age, severe-to-profound hearing-impaired children. Methods: We conducted a controlled before–after study involving 728 severe-to-profound prelingual hearing-impaired children, including an intervention group (n = 60), control group (n = 30), and baseline study group (n = 638). Language scores of the participants and questionnaires to the caregivers/therapists were compared before and after the intervention. Average monthly increase in each language score of the control group and baseline study group were compared with those of the intervention group. Results: Language scores and the results of the questionnaire of the intervention group showed a significant improvement ( P < .05). The average monthly language growth of the intervention group was twice that of the control group and 3 to 4 times that of the baseline study group ( P < .05). The effect size was largest in communication (1.914), followed by syntax (0.931). Conclusion: Domain-based language training improved the language development and daily communication of hearing-impaired children without any adverse effects.